2021
DOI: 10.1038/s41598-021-84964-6
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the benzoate metabolism by human gut microbiome indicates food-derived metagenome evolution

Abstract: Sodium benzoate is one of the widely used food preservatives and its metabolism in the human body has been studied only with the host perspective. Despite the human gut microbiome being considered as a virtual human organ, its role in benzoate metabolism is yet to be elucidated. The current study uses a multi-omic approach to rationalize the role of human gut microbes in benzoate metabolism. Microbial diversity analysis with multiple features synchronously indicates the dominance of Bacteroidetes followed by F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…4h ). Benzoate is a well-known antibacterial agent [ 51 ], and a recent study revealed that its catabolic pathways exist in human gut metagenomic datasets [ 52 ], and antimicrobial food additives induce enrichment of their catabolic pathways at the metagenomic level [ 53 ]. Likewise, we may argue that rejuvenated mice are more resistant to benzoate than aged mice.…”
Section: Discussionmentioning
confidence: 99%
“…4h ). Benzoate is a well-known antibacterial agent [ 51 ], and a recent study revealed that its catabolic pathways exist in human gut metagenomic datasets [ 52 ], and antimicrobial food additives induce enrichment of their catabolic pathways at the metagenomic level [ 53 ]. Likewise, we may argue that rejuvenated mice are more resistant to benzoate than aged mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, a majority of these studies were primarily focused on determining the phylogenetic affiliation of the residing microbes (Naghoni et al, 2017) and provide very limited information about the microbiome functioning (Sorokin and Kuenen, 2005). Metagenomics allows direct access to the genetic content of the microbiome to describe its composition and physiological functions (Ahmed et al, 2018;Yadav et al, 2021). Therefore, metagenomics was used to study the Sambhar Lake microbiome's adaptation, survival, and physiological functions in such a harsh environment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the abovementioned feature, several protein features were identified especially for the quorum sensing and chemotaxis with a possible role in the microbial communication and growth of biofilms, as described by various studies (Waters and Bassler, 2005). Merely the presence of protein features could not confirm their functions, hereby a translation approach like metabolomics could be used to decode functional metabolic pathways by metabolite profiling (Yadav et al, 2020(Yadav et al, , 2021. Identification of metabolites associated with adaptive physiology, as well as with general cell physiology confirms their functions in the lake microbiome (Supplementary Table 8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations